Hierarchical biointerfaces with lotus leaf-like topography for high efficient capture of circulating tumor cells. (24th May 2019) - Wu, Xingda; Chen, Hongpeng; Cai, Ziqing; Liu, Cuijuan; Qiu, Jiehong; Li, Ying; Peng, Xinsheng; Tang, Nan
Abstract: TiO2 films with lotus leaf-like topography were fabricated as hierarchical biointerfaces for efficient capture of cancer cells. Compared to mono-micro or nano-biointerfaces, these hierarchical biointerfaces exhibited a higher cell-capture efficiency, which was attributed to the synergistic effect of micropillar and nanowire arrays. The micropillars provided a large number of potential attachment sites for cancer cells, while nanostructures introduced topographic interaction between cells and the biointerface. The synergistic effect between micropillar and nanowire arrays enhanced the cell-material interaction, and therefore these hierarchical biointerfaces appeared more favorable for cell attachment, spreading and proliferation. These results may provide promising guidance to design or optimize the surface structure of biointerfaces for biomedical application.